A General View of the Role of Specific nutrients in the Prevention of Cardiovascular Diseases - Maralla, Swaroopa.; Bharathi, D (Journal of Drug Delivery and Therapeutics, 2018)
Nearly, 15.3 million people are estimated to die from cardiovascular diseases every year; and this represents one-third of all global deaths from all causes. Lifestyle factors, including nutrition, play an important role in the etiology of Cardiovascular Disease (CVD). A high intake of dietary fats strongly influences the risk of developing cardiovascular disease (CVD). Diet offers incredible opportunities for prevention of cardiovascular disease. Dietary patterns are useful for reducing CVD risk factors, and some have also shown a favourable effect on plaque regression and CVD mortality. Thus, every patient need to adopt a dietary approach that conforms to his or her personal preferences; however, implementing relevant and successful dietary changes is the greatest challenge for preventive cardiovascular medicine.Keywords: Dietary Patterns, Cardiovascular Disease, Risk Factors, Mortality and Preventive Cardiovascular Medicine.